Diversity in the Hawaiian endemic genus Neurisothrips (Thysanoptera, Thripidae) - Mound, Laurence A. (Zootaxa, 2020)
The genus Neurisothrips is known only from the Hawaiian Islands, where it has radiated into a considerable number of species. No other species of the worldwide family Thripidae is endemic to Hawaii, and the lack of structural diversity amongst the members of this genus might suggest that they are derived from a single ancestral introduction. The phylogenetic relationships of Neurisothrips are unclear, but it is possibly derived from Frankliniella, the most species-rich Thripidae genus on the American continent. A key is provided to 14 recognised species of which the following seven are newly described: N. bidens sp. n., N. fran sp. n., N. janis sp. n., N. karl sp. n., N. robbiei sp. n., N. saki sp. n., N. tsuda sp. n. The type species of the genus, N. multispinus (Bagnall), is known only from five fragmented specimens, and its identity remains in doubt. Since each of the species is known only from adults the true host associations remain unclear, but these thrips seem to live primarily on plants that are endemic to the Hawaiian Islands, with N. saki breeding only on the young croziers of Cibotium species, a native fern genus.